Civic Education as Economic Infrastructure: The Way Towards Economic Development - Patimo, Raffaella (European Scientific Journal, ESJ, 2025)
Respect for rules is a structural pillar of well-functioning societies and modern economies, serving as a prerequisite for stability, trust among economic actors, and sustainable development. However, compliance cannot be assumed to arise spontaneously or emerge only when convenient. Rather, it is the result of long-term educational and cultural processes deeply embedded in social institutions, most notably the family and the school system. This paper explores the importance of educating individuals to respect rules as a strategic investment in collective well-being, social cohesion, and institutional quality. Drawing on an institutionalist perspective, it argues that when rule compliance is learned early and through consistent experiences, it fosters trust in institutions, civic engagement, and economic legality. Family and School - as the primary interface between individuals and the normative system - play a crucial role in shaping both civic and social capital. Scholars such as Heckman, North, Acemoglu, and Nussbaum have shown that investments in early childhood education and schooling have positive effects on economic productivity, crime reduction, and democratic participation. If well-designed and widely implemented, education for rule compliance can strengthen the moral and economic foundations of contemporary democracies, promoting a model of development that is fairer, more inclusive, and sustainable. This contribution aims to reaffirm the centrality of education policies - especially those focused on respect for rules and people - as tools for preventing illegality and driving development. It emphasizes the need for coordinated efforts among schools, families, and public institutions to build a citizenry that is aware, cooperative, and respectful of the rules that govern both economic and social life.